Analisis Keterampilan Berpikir Kritis Siswa Melalui Pendekatan Pembelajaran Berbasis Masalah - Yusrol Hana (https://journal.metanusantara.com/pedagogia, 2025)
Critical thinking skills are essential competencies that must be possessed by students in facing the challenges of the 21st century. The Problem Based Learning Approach (PBL) is considered an effective method of developing this skill. This study aims to analyze students' critical thinking skills through the application of PBL in Junior High Schools in Cepu, Indonesia. This type of research is quantitative research with a quasi-experimental experimental approach. The data source in this study was a class VIII student of the two classes randomly selected as an experimental group and the control group. Data is collected using critical thinking skills tests given before and after pre-test (pre-test and post-test). The purpose of this study is to identify the extent to which the application of PBL can improve students' critical thinking skills. The results showed that there was a significant increase in students' critical thinking skills in the experimental group compared to the control group. The average post-test score of the experimental group increased significantly from 55 to 78, while the control group only increased from 56 to 62. T-test statistical tests showed a significance value of 0.001 (p <0.05). The results of this study support constructivist theory and social learning theory that emphasizes the importance of active learning and social interaction in the learning process. The application of PBL has proven effective in developing students' critical thinking skills, so it is recommended for educators to implement this method in their learning.